Combatting Climate Change: Involving Indigenous Communities - Rahman, Serina (2016)
Climate change combat is often in the hands of policy-makers, researchers and governments. However it is the marginalised and indigenous communities that feel the full force of climate change effects. To be effective the campaign needs to include the wisdom and traditional practices of these communities to better protect those who need it the most.